Pengaruh Pemberian Jus Buah Naga Terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil Trimester III dengan Anemia: Literature Review - Munawaroh, Nur Rizki; Sukyati, Ira (Maternal & Neonatal Health Journal, 2025)
Anemia is a condition in which the number of red blood cells or the concentration of hemoglobin in it is lower than normal. Efforts to meet the iron needs of pregnant women in 2 ways, namely non-pharmacologically by giving blood-boosting tablets or multiple micronutrient supplements and pharmacologically by giving dragon fruit juice. To determine the effect of dragon fruit juice on increasing hemoglobin levels in pregnant women in the third trimester with anemia. The research method used is a literature review based on analysis and synthesis of previous studies with a total of five articles published in 2020-2025. Based on the five articles reviewed, giving dragon fruit juice as much as 200cc - 250cc per day for 14 days routinely to increase hemoglobin levels in pregnant women because dragon fruit juice contains quite high iron and vitamin . Dragon fruit juice is effective in increasing hemoglobin levels in pregnant women in the third trimester with anemia.